Recommencement of football competition with spectators during the active phase of the COVID-19 pandemic in a Middle Eastern country - Khan, N. A.; Al Musleh, A. A.; Abdurahiman, S.; Asim, M.; El-Menyar, A.; Al-Thani, H. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: With the global spread of COVID-19 infection caused by the severe acute respiratory syndrome coronavirus-2 virus (SARS-CoV-2), all the national and international sports events were ceased early in 2020. The sport activities have been reinstated since then, albeit without spectators. However, several governments have established a variety of risk-mitigation measures to gradually reintroduce the spectators to stadiums. Objectives: We aimed to evaluate the implementation of a strict health protocol to ensure the resumption of professional football with spectators and to access its effectiveness in limiting the spread of COVID-19 infections within the community. Methods: This was a retrospective, observational study involving football players, match officials, local organizing committee members, working in close coordination, and over 16,000 spectators in the state of Qatar. We examined data from the Amir Cup final (December 18th, 2020), which was played under a strict protocol that included extensive reverse transcription-Polymerase chain reaction (RT-PCR) testing for players and match officials, as well as the utility of COVID-19 rapid antigen and antibody testings as screening tools for spectators to ensure their safe return to the stadiums. In addition, we reviewed the guidelines and protocols that were put in place to organize Qatar's Amir Cup Football Final, which drew over 16,000 spectators in the stadium. Results: A total of 16,171 spectators undertook rapid antigen and antibody tests for the Amir cup final (from December16-December18, 2020). Fifteen Spectators (n = 15) returned with a positive result for COVID-19 infection during the final event (positivity rate = 0.12%). All players underwent RT-PCR testing 48 h before the match. None of the players tested positive for COVID-19 infections. 1311 individuals reported having symptoms related to COVID-19 post final of Amir Cup. These spectators were tested for COVID-19 RT-PCR with an overall positivity rate (positive/reactive) to be 0.42% (69/16171). Conclusion: This report shows a meagre incidence rate of COVID-19 infections during and post-Amir Cup football final. Based on the low infectivity rate reported during and post the Amir Cup, we propose that supervised and controlled resumption of football matches with spectators can be carried out safely following a strict testing and tracing protocol. Similar infection control policies can be replicated with a higher number of spectators.